[PAL pilot ; Guian ; Burger Wars [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
The making of a PAL pilot, aviation school and the rigors of making the grade. Looks at the disaster relief operations in a town in Western Samar that is periodically ravaged by typhoons.